2014
DOI: 10.1097/mol.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the DNA methylome of atherosclerosis

Abstract: Epigenetics continues to represent a promising area of research in atherosclerosis. The full exploitation of cutting edge epigenomics will be decisive to define whether epigenetics will contribute to lower the burden of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In particular, changes in DNA methylation patterns have been linked to several cardiovascular-related biomarkers, including homocysteine and C-reactive protein 9 . Furthermore, an increasing number of studies report DNA methylation alterations in atherosclerosis 24–26 . For example, a recent genome-wide study showed DNA methylation differences between healthy donor-matched aortic healthy and plaque tissue, indicated by epigenetic drift of DNA methylation in aortic plaques with atherosclerotic progression 22, 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, changes in DNA methylation patterns have been linked to several cardiovascular-related biomarkers, including homocysteine and C-reactive protein 9 . Furthermore, an increasing number of studies report DNA methylation alterations in atherosclerosis 24–26 . For example, a recent genome-wide study showed DNA methylation differences between healthy donor-matched aortic healthy and plaque tissue, indicated by epigenetic drift of DNA methylation in aortic plaques with atherosclerotic progression 22, 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These novel concepts, for the first time, associate genetic variations with epigenetic changes. The interaction between genetic variants and DNA methylation also emphasize the need for an integrated study [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that variations in Chr9p21 may increase the levels of ANRIL transcription, which in turn downregulate CDKN2A/2B expression and enhance cell proliferation, and subsequently promote atherosclerosis 14, 15) . Studies also confirmed that ANRIL could bind and recruit epigenetic modifiers to CDKN2A/2B and induce DNA methylation 16, 17) .…”
Section: Introductionmentioning
confidence: 78%